Deformation of Post‐Spinel Under the Lower Mantle Conditions. Issue 3 (14th March 2022) - Xu, F.; Yamazaki, D.; Hunt, S. A.; Tsujino, N.; Higo, Y.; Tange, Y.; Ohara, K.; Dobson, D. P.
Abstract: To study the viscosity of bridgmanite and ferropericlase aggregate, uniaxial compression deformation experiments on pre‐synthesized post‐spinel phase and bridgmanite two‐layered samples were conducted under top lower mantle pressure and 1773 K utilizing DT‐Cup apparatus. Up to the strain of 0.25 ± 0.05, the observed comparable strain of the bridgmanite and post‐spinel samples suggests the bridgmanite dominates the bulk viscosity of the post‐spinel without strain localization in periclase. The microstructures of the deformed post‐spinel samples show evidence of a similar strain of periclase with the bulk strain without strain partitioning. Texture analyses of bridgmanite indicate a dominant slip plane (100), with a steady state fabric strength achieved within the strain of 0.12 ± 0.01. The current experiment has provided no evidence about an onset of strain localization of ∼30 vol.% periclase at 0.25 strain. Our observations provide direct experimental verification of bridgmanite controlled rheology under low strain magnitude, which should be considered in geodynamical models which include mantle compositional and rheological evolution in the lower mantle. Plain Language Summary: The Earth's lower mantle occupies ∼65% volume of Earth's mantle and plays an important role in mantle dynamics. The major constituent mineral of the lower mantle, bridgmanite, might dominate the rheology of the lower mantle. On the other hand, despite its small proportion, there is a chance that ferropericlase controls the rheology of the lower mantle due to its significant softness compared with bridgmanite. In this study, we conducted uniaxial deformation experiments on pre‐synthesized post‐spinel (∼70% bridgmanite +∼30% periclase) and bridgmanite two‐layered samples under top‐most lower mantle conditions up to the strain of 0.25 ± 0.05. The bridgmanite and post‐spinel samples showed similar strains, suggesting that the bridgmanite controls the bulk strength of the post‐spinel. This result is significant for understanding the viscosity structure of Earth's lower mantle. Key Points: Deformation experiments were conducted on pre‐synthesized post‐spinel and bridgmanite two‐layered samples using DT‐Cup apparatus No strain localization was observed in deformed post‐spinel up to the strain of 0.25 ± 0.05 Bridgmanite dominates the bulk rheology of post‐spinel under the current experimental conditions